The Self-Efficacy and Stress Symptoms in Schools - Reza Fahmi; Prima Aswirna; Desrimayeni Desrimayeni (Universitas Islam Negeri Ar-Raniry Banda Aceh, Aceh, Indonesia., 2021)
This research departs from the fact that many students feel pressured by many assignments at school, and this causes their stress symptoms to experience at school. Therefore the ability to solve problems (self-efficacy) is thought to be very important to deal with these problems. The purpose of this study is to examine the relationship between self-efficacy and stress symptoms of elementary school students (Madrasah Ibtidaiyah Private) in Solok City, West Sumatra. This research uses a quantitative approach, with a population of 354 students. However, only grades 4-6 were included in this study as a sample totaling 80 people. The sampling technique used is proportional to stratified soak sampling. The statistical model used in this study is the Pearson correlation. The results of this study prove the relationship between self-efficacy and stress symptoms of elementary school students.